Biology of Inflammation in Crohn's Disease: Mechanisms of Action of Anti-TNF-αAlpha Therapy - Stephan R Targan (Canadian Journal of Gastroenterology)
Several recent trials of intravenously administered antitumour necrosis factor-alpha (TNF-α) monoclonal antibody have shown dramatic responses among patients with Crohn’s disease. These results indicate a primary role for TNF-αin the mediation of altered mucosal immune function in this disease. Clinical responses in patients treated with a single infusion of anti-TNF-αpersisted for as long as one year. The prolonged period of clinical benefit shows that the effect of short term TNF-αelimination remains long after the monoclonal antibody has cleared the body. Corresponding in vitro investigation has shown that T helper 1 (Th1) -mediated cytokine production of interferon-gamma is downregulated in the involved mucosa to a level consistent with that seen in uninflamed mucosa. These results suggest that TNF-α-specific augmentation of mucosal Th1 function is the process that is altered by removal of TNF-αand that produces such persistent responses. Understanding how TNF-αmodulates mucosal Th1 function may lead to the definition of a key feature of Crohn’s disease pathogenesis.